NURSES' ATTITUDE TOWARDS PATIENTS WITH MENTAL ILLNESS IN A TERTIARYCARE HOSPITAL - HAYDER , S; ANDLEEB , S; AHMED , S (Biological and Clinical Sciences Research Journal, 2024)
Nurses play a crucial role in the care of patients with mental illness, yet their attitudes towards these patients can significantly impact the quality of care provided. This study aimed to assess nurses' attitudes towards patients with mental illness in a general hospital setting. A cross-sectional survey was conducted among 150 nurses working in various hospital departments. The Attitudes Towards Mental Illness (ATMI) scale was utilized to measure nurses' attitudes. Results revealed that most nurses held positive attitudes towards patients with mental illness, with a mean ATMI score of 75.4 (SD=6.8) out of 100. However, a subgroup analysis identified variations in attitudes based on nurses' years of experience and department of work. Nurses with more years of experience tended to exhibit more positive attitudes toward mental illness. At the same time, those working in acute care settings showed slightly more negative attitudes compared to those in psychiatric units. These findings underscore the importance of addressing nurses' attitudes towards mental illness to ensure the delivery of high-quality and stigma-free care to patients with mental health conditions.